Influence of saline-tolerant arbuscular mycorrhizal fungi on rice growth under varying salinity levels - Nadaf, M N; Jones, N P; Navi, V; Hosmath, J A (Plant Science Today, 2026)
An investigation was conducted from 2022 to 2024 examined native arbuscular mycorrhizal (AM) fungi in the saline wetland rice ecosystems of the Aghanashini and Kagal regions in the Uttara Kannada district, Karnataka, India. Between the two sites, Aghanashini recorded higher AM fungal diversity across all diversity indices, including the Shannon-Wiener diversity index, Margalef’s species richness index and Simpson’s dominance index. Three efficient AM fungal isolates–UASDAMFAG8 (Acaulospora mellea), UASDAMFAG10 (Glomus macrocarpum) and UASDAMFAG28 (Glomus aggregatum)–were selected based on their superior performance in phosphorus uptake, total dry biomass production and peroxidase activity in rice grown under salinity levels of 6 and 8 dS m-1 respectively. These isolates were evaluated individually and in combination under controlled microcosm conditions. The AM fungal consortium (G. macrocarpum + A. mellea + G. aggregatum) significantly enhanced plant growth parameters, mycorrhizal root colonization, total glomalin content, relative chlorophyll content, proline accumulation, phosphorus uptake and soil enzyme activities compared to the uninoculated control (UICNotably, the consortium increased proline content in rice to 13.47 and 14.06 μmol g-¹ fresh weight (FW) under 6 and 8 dS m-¹ salinity respectively. Among individual inoculants, G. macrocarpum showed the most pronounced effects across all measured parameters. The statistical interaction between AM fungi and salinity stress revealed that the AM fungal consortium effectively mitigated the adverse effects of salinity at both levels. These findings suggest that native AM fungal isolates, particularly in consortium form, can be exploited for enhancing salt tolerance and promoting sustainable rice cultivation in saline wetland ecosystems.